Parameters determination of mobile robot of LEGO MINDSTORMS® - Pinto-Salamanca, María Luisa; Bermúdez-Bohórquez, Giovanni Rodrigo (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2007)
It  presents the study and application of the system identification's technologies and the development of experiments to determine the parameters and geometric characteristics of a mobile robot of differential configuration, constructed with pieces from the  robotics kit  LEGO MINDSTORMS®, as example for the determinate the required parameters  in any robotic mobile platform of differential configuration.